ACQUIRED REFRACTORY IRON DEFICIENCY - Margherita Migone De Amicis; Alessandro Rimondi; Luca Elli; Irene Motta (Mediterranean Journal of Hematology and Infectious Diseases)
Anemia is a global health problem affecting one-third of the world population, and half of the cases are due to iron deficiency (ID). Iron de?ciency anemia (IDA) is the leading cause of disability in several countries. The causes of ID and IDA can be classified as i) insufficient iron intake for the body requirement, ii) reduced absorption, and iii) and blood losses, although multiple mechanisms may coexist. Oral iron represents the mainstay of IDA treatment. IDA is defined as "refractory" when the hematologic response after 4 to 6 weeks of treatment with oral iron (an increase of <1 g/dL of Hb) is absent. The cause of iron-refractory anemia is usually acquired and frequently related to gastrointestinal pathologies, although a rare genetic form called iron refractory iron deficiency anemia (IRIDA) exists. In some pathological circumstances, either genetic or acquired, hepcidin is increased, limiting the absorption in the gut, remobilization, and recycling of iron, thereby reducing iron plasma levels. Indeed, conditions with high hepcidin levels are often underrecognized as iron-refractory, leading to inappropriate and unsuccessful treatments. This review provides an overview of the conditions underlying iron-refractory anemia, from gastrointestinal pathologies to hepcidin dysregulation and iatrogenic or provoked conditions, and the specific diagnostic and treatment approach.